1996
DOI: 10.1002/(sici)1097-0290(19960305)49:5<481::aid-bit1>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Coculture of genetically transformed roots and shoots for synthesis, translocation, and biotransformation of secondary metabolites

Abstract: Genetically transformed shooty teratomas of Atropa belladonna and a Duboisia leichhardtii X D. myoporoides hybrid were studied for biotransformation of tropane alkaloids in shake flasks and bioreactors. Although de novo synthesis of hyoscyamine and scopolamine was limited, shoots of both species were able to translocate and accumulate significant quantities of exogenous alkaloid. The maximum yield of scopolamine from hyoscyamine fed to the Duboisia hybrid shoots was 35% w/w; the yield of the scopolamine precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Co-culture of root and shoot has beed used previously to improve production of tropane alkaloids in Atropa belladonna and a Duboisia leichhardtii × D . myoporoides hybrid plants [51]. The significant increase in nornicotine production by Ntom CYP82E4 when co-cultivated with Ntab MPO1 cells demonstrated that the physical presence of cells was superior to just feeding the conditioned medium collected from the same cells (Fig 8).…”
Section: Discussionmentioning
confidence: 99%
“…Co-culture of root and shoot has beed used previously to improve production of tropane alkaloids in Atropa belladonna and a Duboisia leichhardtii × D . myoporoides hybrid plants [51]. The significant increase in nornicotine production by Ntom CYP82E4 when co-cultivated with Ntab MPO1 cells demonstrated that the physical presence of cells was superior to just feeding the conditioned medium collected from the same cells (Fig 8).…”
Section: Discussionmentioning
confidence: 99%
“…This study represents an extension of previous work in which single‐ and cross‐species coculture of hairy roots and shooty teratomas was used to enhance the production of scopolamine in vitro (25, 26). Because neither hairy roots nor shooty teratomas require exogenous growth regulators, the choice of medium for this type of coculture is relatively straightforward.…”
Section: Discussionmentioning
confidence: 96%
“…The procedure used for analysis of tropane alkaloids was based on that described by Subroto et al (1996). Ion-pair HPLC was carried out using a reverse-phase column (Alltima C 8, 5 ~tm, 250 mmx 4.6 mm; Alltech, USA) operated at ambient temperature with UV detection at 205 nm.…”
Section: Analysesmentioning
confidence: 99%